America is under attack : September 11, 2001 : the day the towers fell - Brown, Don, 1949- (Brown, Don, 1949- Actual times ;, 2011)
Narrates the terrorist attacks on the United States on September 11, 2001, from the plane hijackings to the collapse of the World Trade Center.